2007
DOI: 10.1590/s0103-84782007000400039
|View full text |Cite
|
Sign up to set email alerts
|

Estimativa da área foliar de meloeiro em estádios fenológicos por fotos digitais

Abstract: RESUMO O objetivo deste trabalho foi avaliar a precisão do método de fotos digitais na estimativa da área foliar de meloeiro e encontrar modelos matemáticos de estimativa da área foliar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
2
13

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 3 publications
1
11
2
13
Order By: Relevance
“…In contrast to the results obtained by Tavares Júnior et al (2002) and Dombroski et al (2010), who compared the digital scanner method with the leaf disc method, we concluded that the LA was overestimated in the leaf disc method. Dombroski et al (2010), working with a pine cone culture, used a correction factor (0.894) to balance the overestimation of LA by the leaf disc method. In a study that used Chrysobalanus icaco, Cunha et al (2010) found a high coefficient of determination (R² = 0.978) and a high angular coefficient (0.994) between the digital scanner and the leaf disc methods.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to the results obtained by Tavares Júnior et al (2002) and Dombroski et al (2010), who compared the digital scanner method with the leaf disc method, we concluded that the LA was overestimated in the leaf disc method. Dombroski et al (2010), working with a pine cone culture, used a correction factor (0.894) to balance the overestimation of LA by the leaf disc method. In a study that used Chrysobalanus icaco, Cunha et al (2010) found a high coefficient of determination (R² = 0.978) and a high angular coefficient (0.994) between the digital scanner and the leaf disc methods.…”
Section: Resultscontrasting
confidence: 99%
“…In addition, this finding partially clarifies the differences between the present and past research results. The underestimation of LA in the present study is proportional to or smaller than the overestimation that was observed in other studies, such as those by Dombroski et al (2010), Marrocos et al (2010) and Lucena et al (2011).…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…There are nondestructive methods for LA determination using simple and easily operated devices that preserve leaf integrity (Adami et al, 2008;Fagundes et al, 2009;Bakhshandeh et al, 2011). Some examples are models generated for tomato and cucumber (Blanco & Folegatti, 2003), melon (Lopes et al, 2007), sunflower (Maldaner et al, 2009) and crambe (Toebe et al, 2010).…”
Section: Introductionmentioning
confidence: 99%